2018
DOI: 10.1021/acs.iecr.7b02841
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study for Vapor Phase Aldol Condensation of Methyl Acetate and Formaldehyde over Alkali Metal Oxides Supported on SBA-15

Abstract: Alkali metal oxides supported on SBA-15, M/ SBA-15 (M = Li, Na, K, Rb, and Cs), prepared by the impregnation method were characterized and tested for the aldol condensation of methyl acetate and formaldehyde to methyl acrylate (MA). M/SBA-15 catalysts are active for the formation of MA while the support is inert. The supported alkali metals react with hydroxyl groups on SBA-15 by replacing the H atoms and generate weak and medium basic sites. The latter plays an important role in promoting the reaction. Coke f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…19−22 Alkali metal catalysts supported on silica or SBA-15 were studied for aldol condensation and their catalytic activity is increased as the order of basicity Li < Na < K < Cs. 23,24 A similar study was also conducted by Ai using the cesium based catalysts, which showed higher activity than any other metal-based catalysts. 25,26 Through in-depth investigation of condensation of MP with FA, Ai discovered that acid sites were beneficial to improve the selectivity, whereas the base sites were good for increasing conversion.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…19−22 Alkali metal catalysts supported on silica or SBA-15 were studied for aldol condensation and their catalytic activity is increased as the order of basicity Li < Na < K < Cs. 23,24 A similar study was also conducted by Ai using the cesium based catalysts, which showed higher activity than any other metal-based catalysts. 25,26 Through in-depth investigation of condensation of MP with FA, Ai discovered that acid sites were beneficial to improve the selectivity, whereas the base sites were good for increasing conversion.…”
Section: Introductionmentioning
confidence: 82%
“…As described before, Cs-based catalysts performed excellent catalytic activity, and P could be used as the good support stabilizer. 23,24 Nevertheless, this optimized catalyst did not perform better in the reaction between MP and FA because of the improper or unbalanced acid−base properties.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[23][24][25][26] The mesoporous composite metal oxides-SBA-15 materials have high surface area, ordered mesopores, and redox catalytic sites, have attracted extensive research attention as effective and low cost catalysts in heterogeneous catalysis. [27][28][29][30][31] Because of the special structure and their potential catalytic activities they exhibit, these compounds have distinguished themselves as catalysts of profound chemical significance. Therefore, preparing these ordered mesoporous materials and investigating their catalytic performance in organic synthesis has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the chemical inertness of SBA‐15, which is mainly composed of silicon dioxide, greatly limits its application in chemical engineering, especially in heterogeneous catalysis [23–26] . The mesoporous composite metal oxides‐SBA‐15 materials have high surface area, ordered mesopores, and redox catalytic sites, have attracted extensive research attention as effective and low cost catalysts in heterogeneous catalysis [27–31] . Because of the special structure and their potential catalytic activities they exhibit, these compounds have distinguished themselves as catalysts of profound chemical significance.…”
Section: Introductionmentioning
confidence: 99%